ANALISIS PENGARUH CORPORATE GOVERNANCE PERCEPTION INDEX, UKURAN PERUSHAAN DAN LEVERAGE TERHADAP FINANCIAL DISTRESS : STUDI EMPIRIS PADA PERUSAHAAN PESERTA CGPI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016 - Mufti Gilang; Darsono Darsono (Diponegoro Journal of Accounting, 2019)
This aims of this study is to examine the effect of corporate gorvernance perception index, company size, and leverage on the occurrence of financial distress in a company. In the previous study, there was a relationship between the company's financial performance and the occurrence of financial distress in the company.In this research, the population listed on the Indonesia Stock Exchange period 2012-2016 and also listed in the announcement of the results of research conducted by the Institute for Corporate Governance (IICG) to obtain CGPI scores. The method to sample selection using the purposive sampling method. Analysis of the data used is descriptive statistics, classical assumption test and hypothesis testing with correlation methods and multiple regression tested using SPSS 23 software.The results of the hypothesis proved that the variable firm size and leverage base significantly affect financial distress. while the CGPI variable had no significant effect on the occurrence of financial distress.